Kinetics of Mushroom Tyrosinase and Melanogenesis Inhibition by N-Acetyl-pentapeptides. (21st July 2014) - Lien, Ching-Yi; Chen, Ching-Yu; Lai, Shih-Ting; Chan, Chin-Feng
Abstract : We investigated the kinetics of 4 N -acetyl-pentapeptides, Ac-P1, Ac-P2, Ac-P3, and Ac-P4, regarding inhibition of mushroom tyrosinase activity. The peptides sequences of Ac-P1, Ac-P2, Ac-P3, and Ac-P4 were Ac-RSRFK, Ac-KSRFR, Ac-KSSFR, and Ac-RSRFS, respectively. The 4 N -acetyl-pentapeptides were able to reduce the oxidation of l -DOPA by tyrosinase in a dose-dependent manner. Of the 4 N -acetyl-pentapeptides, only Ac-P4 exhibited lag time (80 s) at a concentration of 0.5 mg/mL. The tyrosinase inhibitory effects of Ac-P4 (IC50 0.29 mg/mL) were more effective than those of Ac-P1, Ac-P2, and Ac-P3, in which IC50 s were 0.75 mg/mL, 0.78 mg/mL, and 0.81 mg/mL, respectively. Kinetic analysis demonstrated that all 4 N -acetyl-pentapeptides were mixed-type tyrosinase inhibitors. Furthermore, 0.1 mg/mL of Ac-P4 exhibited significant melanogenesis inhibition on B16F10 melanoma cells and was more effective than kojic acid. The melanogenesis inhibition of Ac-P4 was dose-dependent and did not induce any cytotoxicity on B16F10 melanoma cells.